Theoretical Study of Cluster Emission and Fission Dynamics Using Binary Fragmentation Approach - Sharma, Kanishka (My University, 2019)
The principal objective of the present work is to explore the various ground state decay processes having different disintegration mechanisms on the basis of their structural properties. These radioactive decay modes include -radioactivity, cluster emission, heavy particle decay and spontaneous fission of parent nuclei. The study has been carried out using the methodology of Preformed Cluster Model (PCM). Beside this, predictions on Snradioactivity and Heavy-Particle Radioactivity (HPR) have been made for the validation of the present calculations via future experiments. Furthermore, an extensive analysis on heavy-ion induced fission of heavy nuclei is carried out in view of their mass distribution and the cross-sectional analysis. The calculations of excited state decays are accomplished within the framework of Dynamical Cluster-decay Model (DCM), the extended version of PCM with temperature and `-effects included. The role of center of mass energy, angular momentum, deformations and orientations is investigated comprehensively in order to gain the useful information on induced fission phenomenon. Additionally, a comprehensive analysis has been done so as to compare the ground state and excited state decay mechanisms in view of their respective structural and barrier profiles.
Keywords: Radioactivity; Cluster Decay; spontaneous fission; half-lives; deformations